Analisis Penilaian Bahan Ajar Buku Siswa Bahas Arab (Pendekatan BSNP) Kelas 10 Madrasah Aliyah Terbitan Kementerian Agama Republik Indonesia 2020 - Siti Aprilyanti; Hafidah Hafidah (Uktub: Journal of Arabic Studies, 2023)
Teaching materials are an important component in realizing the goals of teaching and learning activities. Teaching materials will work effectively if they are adapted to other components, such as teaching materials, achievement indicators and learning objectives. Of course this needs to be optimized so that teaching materials have a very large influence on teacher performance and the quality of students. So, complex teaching materials are teaching materials that get good assessment results. While the phenomenon that occurs is the teacher relies on how to spend the material. This study aims to determine the assessment of Arabic textbooks for class 10 published by the 2020 Ministry of Religion from the perspective of the BSNP. In this study using a qualitative method with the type of library research, namely obtaining information on the criteria for evaluating teaching materials that are correct and good from all reading and recording activities, in the form of books, journals, articles, survey results, seminar materials and other research results. Product development in this research is product development in the form of Grade 10 Arabic Textbooks published by the Ministry of Religion 2020 from the BSNP perspective. The results of this study include: After reviewing various literature on the criteria for evaluating good teaching materials, it can be concluded that the assessment of good teaching materials, especially textbooks, must meet four criteria, namely First, the contents of the book (material), Second, Presentation, Third, Linguistics, and Fourth, Graphics in a learning concept, especially in Arabic subjects.